Industrial-grade nitrogen sources modulate CaCO3 polymorphs and strength in MICP-cemented sand: A structure–property study - Yu Zhang; Xu Zhang; Bo Peng; Yongzhi Zhang; Zherui Chen; Guohui Ma; Jin Wang; Qiang Wen; Miao Liu (PLoS ONE, 2026)
Microbially induced carbonate precipitation (MICP) is promising for soil stabilization. However, its large-scale application is hindered by the cost of laboratory-grade yeast extract (YE), which often accounts for more than 70% of cultivation medium expenses. Here, we evaluate two standardized industrial nitrogen sources—industrial yeast extract (IYE) and soy peptone (SP)—as complete or partial replacements for YE in Sporosarcina pasteurii cultivation. Urease activity and the performance of bio-cemented sand columns were assessed via unconfined compressive strength (UCS), CaCO 3 content, and mineralogical/microstructural analyses. Results indicated that the partial substitution scheme of 5 g/L pure YE + 10 g/L IYE yielded the best overall outcomes: bacterial urease activity reached ~80% of the control, UCS reached 4.27 MPa (9% higher than the control), and the nitrogen-source cost was reduced by 65.53%. The enhanced strength correlates with a favorable precipitation pathway that produced predominant calcite (~95.57% of the CaCO 3 precipitate), together with a dense, interlocking microstructure. In contrast, SP-substituted media produced lower UCS despite a high CaCO 3 content (up to 15.31%), indicating that mechanical performance depends not simply on the total amount or final polymorph of CaCO 3 , but on the combined effects of polymorph composition, precipitation pathway, and the resulting microstructural organization. Overall, the proposed YE–IYE blending strategy offers a practical route to lower-cost, higher-performance MICP sand stabilization.